Covariation between the cranium and the cervical vertebrae in hominids. Issue 162 (January 2022) - Arlegi, Mikel; Pantoja-Pérez, Ana; Veschambre-Couture, Christine; Gómez-Olivencia, Asier
Abstract: The analysis of patterns of integration is crucial for the reconstruction and understanding of how morphological changes occur in a taxonomic group throughout evolution. These patterns are relatively constant; however, both patterns and the magnitudes of integration may vary across species. These differences may indicate morphological diversification, in some cases related to functional adaptations to the biomechanics of organisms. In this study, we analyze patterns of integration between two functional and developmental structures, the cranium and the cervical spine in hominids, and we quantify the amount of divergence of each anatomical element through phylogeny. We applied these methods to three-dimensional data from 168 adult hominid individuals, summing a total of more than 1000 cervical vertebrae. We found the atlas (C1) and axis (C2) display the lowest covariation with the cranium in hominids ( Homo sapiens, Pan troglodytes, Pan paniscus, Gorilla gorilla, Gorilla beringei, Pongo pygmaeus ). H. sapiens show a relatively different pattern of craniocervical correlation compared with chimpanzees and gorillas, especially in variables implicated in maintaining the balance of the head. Finally, the atlas and axis show lower magnitude of shape change during evolution than the rest of the cervical vertebrae, especially those located in the middle of the subaxial cervical spine. Overall, results suggest that differences in the pattern of craniocervical correlation between humans and gorillas and chimpanzees could reflect the postural differences between these groups. Also, the stronger craniocervical integration and larger magnitude of shape change during evolution shown by the middle cervical vertebrae suggests that they have been selected to play an active role in maintaining head balance.